(untitled) (Лучшие интеллектуальные исследования, 2025)
Every language has specific system which differs from that of any other. This is all the more so with respect to English, Uzbek and Russian, whose grammatical systems are typologically and genetically heterogeneous. English and Russian belong to the Germanic and Slavonic group’s respectively of the Indo – European family of languages; the Uzbek language pertains to the Turkic group of the Altaic family. Concerning the morphological type both English and Russian are inflected, though the former is notable for its analytical character and the latter for its synthetic character in the main. Uzbek is an agglutinative language. The importance of grammar in translating sentences and their meaning are discussed in this article.